The Deployment of Industrial Paternalism in the Compañía Minera E Industrial de Chile (1920-1940) [a Implantação Do Paternalismo Industrial Na Compañía Minera E Industrial de Chile (1920-1940)] [el Despliegue del Paternalismo Industrial en la Compañía Minera E Industrial de Chile (1920-1940)] - Venegas-Valdebenito, H; Morales-Barrientos, D (Universidad de los Andes, Bogota Colombia, 2015)
Within the framework of industrial paternalism this article analyzes the strategies of “extensive” control applied by the coal-mining industries in the district of Lota-Coronel in southern Chile. It studies the policies maintained by the Compañía Minera e Industrial de Chile for the purpose of modifying working-class family life in the locality of Lota Alto. It shows how the company was effective in creating an orderly and aseptic work culture in the mining area. These efforts were aimed at disciplining the labor force, and women were therefore granted an especially important role as the tutors of the household and articulators of the ¨non-work” spaces within the miner’s family group. This work is the result of a detailed analysis of the company’s own records, such as the newspaper La Opinión, and regulations governing daily life in the mining town of Lota. © 2015, Universidad de los Andes, Bogota Colombia. All rights reserved.